Examining chemical composition of gas turbine-emitted organic aerosol using positive matrix factorisation (PMF). (January 2022) - Smith, Liam D.; Allan, James; Coe, Hugh; Reyes-Villegas, Ernesto; Johnson, Mark P.; Crayford, Andrew; Durand, Eliot; Williams, Paul I.
Abstract: In this paper, the characteristics of non-refractory aerosol using an International Civil Aviation Organization (ICAO) compliant sampling system emitted from two gas turbine relevant sources are reported, namely: an in-service turboshaft helicopter engine and a development combustor rig. Positive Matrix Factorisation (PMF) analysis was applied on an Aerosol Mass Spectrometer's (AMS) Unit Mass Resolution (UMR) organic aerosol (OA) data to identify three chemical factors: one unburnt fuel factor (AlkOA; Alkane Organic Aerosol) and two factors formed through oxidative processes: Semi Volatile Oxygenated Organic Aerosol (SV-OOA) and Quenched Organic Aerosol (QOA). The AlkOA factor's mass concentration correlated with Elemental Carbon (EC), an incomplete combustion tracer. The SV-OOA factor's mass concentration correlated with AMS-detected sulphate and Organic Carbon (OC) as characterised by a Sunset semi-continuous Analyser, with a high proportion of the OC converted to CO2 at lower temperatures (≤475 °C) during the OC analysis, suggesting a higher volatility. The QOA factor's mass concentration corresponded with higher quantities of OC converted to CO2 at the highest temperature (870 °C) during the OCEC analysis protocol. The QOA factor comprised large quantities of AMS-detected organic mass concentrations (20–50%) for the IP Rig. In addition, issues were seen with the OCEC analyser, and future strategies for operation for sampling from aviation sources are considered. The work characterises the available chemical speciation present in the particulate matter phase within an ICAO compliant nvPM sampling system for in-service and development combustor rigs, and comparisons are made between mass spectra seen within this methodology and in evolved plumes. Highlights: Composition is examined in a regulatory sampling system for the first time Aircraft organic aerosol was composed of three chemical factors: one unburnt fuel factor and two oxidised aerosol factors. Aerosol composition was comparable with evolved plumes, despite short distances. Possibly due to lower thrusts and 4 meter distances applied. A change to NIOSH5040 protocol on OCEC Analyser is advised for future examination of aviation emissions. High quench air flow in a combustor rig appeared to simulate organic aerosol ageing.